A política de segurança dos Estados Unidos após o 11 de setembro de 2001: a construção da guerra ao terror. - Oliveira, Isaac Anderson de Carvalho (Universidade Federal do Tocantins, 2021)
On September 11, 2001, the United States of America suffered one of the largest terrorist attacks in human history and the largest on American soil. Members of the Muslim group AlQaeda carry out suicide bombings using commercial aircraft as symbols. the country's historical and important history, resulting in an unprecedented tragedy with thousands of victims, a sudden shift in relations between nations and the focus of the global agenda for discussion. It was the beginning of a new period in international relations. The present paper seeks to analyze US security policy after 9/11, looking at the full context of the late Cold War period in relation to US action in the Middle East region and how the country became the target. of the group that carried out these attacks.